Endothelium glutamate receptors in brain pathology - Pirozhkov, Sergey V.; Vukolova, Marina N.; Bulgakova, Varvara V.; Lutokhina, Yulia A.; Bolevich, Sergey B.; Sobolevsky, Alexander I.; Yelshanskaya, Maria V. (Frontiers in Pharmacology, 2025)
The endothelium in brain microcirculation functions not only as a barrier but also as a signal transduction component within a system that regulates multiple vascular processes, including muscle tone, permeability, and structural integrity. The control of local blood flow is vital to ensure adequate oxygen and nutrient supply, efficient removal of catabolic waste, and the maintenance of proper brain cell function. The role of endothelial glutamate receptors in brain pathology is an emerging area of research, particularly important for understanding how these receptors contribute to neurological diseases and disorders. Endothelial cells (ECs), which are considered active players in maintaining brain homeostasis, express glutamate receptors on their surface. Activation of these receptors can trigger a cascade of signaling events, including synthesis of nitric oxide (NO) and proinflammatory molecules. N-Methyl-D-Aspartate receptors (NMDARs) play a significant role in functional hyperemia, also known as neurovascular coupling (NVC), which is essential for maintaining the energy balance in brain cells. Growing evidence suggests that disturbance of this balance is implicated in several neurological diseases, such as Alzheimer’s disease, stroke, and traumatic brain injury (TBI), where endothelial dysfunction may impair blood flow regulation, contributing to further neuronal damage and cognitive decline. This review focuses on the glutamate receptor-mediated alterations in endothelial permeability and the prevention of the brain pathology through direct modulation of these receptors. Notably, the metabotropic glutamate receptor mGluR1, along with NMDARs, may cause deleterious effects in brain ischemia, as their activation increases the permeability of the vessel wall. Stimulation of NMDARs may also lead to ferroptosis in ECs. EC dysfunction results in significant blood-brain barrier (BBB) disruption, allowing infiltration by inflammatory cells and the accumulation in brain of pathological proteins, such as amyloid-beta (Aβ) or autoantibodies. This contributes to neuronal dystrophy and apoptosis, as seen in Alzheimer’s disease and autoimmune encephalopathy. Activated ECs generate proinflammatory mediators that attract leukocytes and sustain the neuroinflammatory response. Infiltrating peripheral white blood cells are key contributors to inflammatory damage following TBI. Regulation of ECs through glutamate receptors therefore represents a promising therapeutic strategy for treatment of neurodegenerative diseases, as well as ischemic and traumatic brain injuries.